Fort Riley and Its Neighbors - William A. Dobak (Symphony in the Flint Hills, 2013)
“Amateurs study strategy; professionals study logistics” is a maxim often attributed to the late General Omar Bradley. Getting supplies to soldiers has been proven to be a challenge throughout history.
Keywords: Ft. Riley; Fort Riley; Junction City; westward; west; Fort Leavenworth; military; army; defense; Sante Fe; Pacific Coast; Smoky Hill River; Kaw River; Kansas; expansion; plains; prairie; grassland; river; navigation; exploration; civillians; railroad; Union; Kansas Pacific Railway; Manhattan; supply; logistics; Mounted Branch School; war; agricultural; agriculture; William T. Sherman; farming; farm; threshing; Dixon Stockyards; ranch; ranching; cows; cowboy; Secretary of War; Davis County; building; construction